Definisi Konflik dan Pentingnya Manajemen Konflik dalam Pendidikan - Wadiv Vatul Khovivah; Maulidatus Sholehah; M. Anshori Saleh; Alivia Ummi Jamilah; Mu’alimin Mu’alimin (Master Manajemen, 2024)
Conflict is a situation where there are differences of opinion or interest between one individual and another individual. This research aims to describe conflict, conflict management, the importance of conflict management and the principles of conflict management in organizations, especially education. The type of research carried out is literature study. Data collection through books, accredited national journals related to research studies. The process of searching for articles and books via Google Scholar, collecting articles and books related to research studies, starting with 3 books with ISBNs about conflict management and 10 national articles. Data analysis used screening by selecting 10 journals and books and then selecting 5 articles to find study topics in more depth. The results of this research are (1) The definition of conflict is a condition that arises when there are differences of opinion or views between individuals, groups or organizations (2) conflict management is constructive action that is planned to regulate situations that should not occur by the parties involved. conflict in organizations (3) Conflict management includes at least three main stages, namely conflict planning analysis, conflict assessment and conflict resolution (4) There are six principles in conflict management so that it does not cause more serious problems.